Question:

If \( A \) denotes the sum of all the coefficients in the expansion of \( (1 - 3x + 10x^2)^n \) and \( B \) denotes the sum of all the coefficients in the expansion of \( (1 + x^2)^n \), then:

Updated On: Jan 25, 2025
  • \( A = B^3 \)
  • \( 3A = B \)
  • \( B = A^3 \)
  • \( A = 3B \)
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is A

Solution and Explanation

To find the sums \( A \) and \( B \), we calculate the sum of all coefficients by setting \( x = 1 \) in each expansion.

Step 1. Calculate \( A \)

Substitute \( x = 1 \) in \( (1 - 3x + 10x^2)^n \):\[ A = (1 - 3 \cdot 1 + 10 \cdot 1^2)^n = (1 - 3 + 10)^n = 8^n \]Therefore, \( A = 8^n \).

Step 2. Calculate \( B \)

Substitute \( x = 1 \) in \( (1 + x^2)^n \):\[ B = (1 + 1^2)^n = 2^n \]Thus, \( B = 2^n \).

Step 3. Find the Relationship Between \( A \) and \( B \)

Since \( A = 8^n \) and \( B = 2^n \), we can write:\[ A = (2^n)^3 = B^3 \]Therefore, \( A = B^3 \).

Was this answer helpful?
1
0